Developmental Changes of Axonal Excitability: Refractory Period Measurement in Normal Children. - Nadeem, Ahmed S. M.; Alwan, Basim M.; Mezaal, Mohammad A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: “The absolute refractory” period is the time interval during which the nerve fiber is in capable of conducting another impulse after a conditioning stimulus and the determination of the refractory period distribution in a nerve can give a good idea about the characteristics of the conducting fibers constituting that nerve as it reflects their excitability and could be used as a sensitive  indicator for the ability of the nerve fiber to conduct pairs of closely spaced impulses.Methods: The new collision test was used to measure precisely the absolute motor refractory period and the paired shock technique to measure the absolute sensory refractory period in the ulnar nerves of 167 normal infants and children to identify age related changes in the excitability of the nerve fiber membrane.Results: These tests showed that changes in the membrane properties of the fastest and the slowest motor and sensory fibers differ with age. Fastest fibers have more prominent and rapid reduction in their absolute refractory periods (increased excitability) at the successive age groups during the period between 6 months to 6years of life, while the slowest ones have more gradual and prolonged membrane changes (as assessed by the dispersion of the refractory periods)Conclusion: These electrophysological findings point to a period of rapid increment in the nerve fiber diameter, myelin thickness and the possibility of addition of new functioning nerve fibers during the process of growth and development, since each fiber has its characteristic absolute refractory period from birth.